Penghasilan enzim tanase oleh penicillium sp. pencilan tempatan secara fermentasi kultur tenggelam - Doblin Anak, Sandal (2017)
The isolate that was used in the production of tannase was identified as Penicillium sp. This isolate was isolated from a R. apiculata barks dumping area, at the mangrove area in Larut-Matang, Perak. Optimization of physical parameters and medium compositions showed an increment of 578% or 4.983 U/ml compared with the activity before optimization which was 0. 735 U/ml. The optimal physical parameters were initial pH 6.0, temperature of 30°C, agitation speed of 170 rpm and inoculum size of 1.0% (v/v) of 1.53 x 106 spores per mi. Meanwhile, optimal medium compositions were {%; w/v) NHCI4, 0.25%; KH2P04, 0.1 %; MgS04.yH20, 0.05%; KCI, 0.05% and tannic acid, 4%. Cell immobilization of Penicillium sp. on sodium alginate beads and nylon sponge cubes produced tannase activity as much as 7.066 U/ml and 5.124 U/ml respectively. The results showed an increment of 44.2% for calcium alginate beads and 4.57% for nylon sponge cubes. Production of tannase by free cells in a tubular air-lift fermenter showed an increment of 71.7% compared to Erlenmeyer shake flask volume 500 ml and 73.5% compared to Erlenmeyer shake flask volume 250 mi. Maximal production of tannase in a tubular air-lift fermenter was 11.76 U/ml with increment of 38.4% before optimization. The optimized production parameters used in the fermenter were 400 of sodium alginate beads, inoculum size at 1.0% (v/v) of 1.53 x 106 spores per ml and aeration of 2.0 wm. Tannase was purified by ammonium sulphate precipitation and gel filtration chromatography using Sephadex G-200, twice. The peak obtained was purified about 44.35 fold with a yield of 0.69% and specific activity of 6.12 U/mg protein. Its molecular weight was estimated to be around 76,1000 Dalton by SDS-PAGE. Crude and purified tannase had the optimum temperature of 40°C and stable at that temperature for 90 minutes and 75 minutes, respectively.